Potential therapeutic effect of thymoquinone on cisplatin-induced hepatotoxicity in rats - Sercan Kaya; Tuba Yalcin (Eurasian Journal of Veterinary Sciences)
Aim: Cisplatin (CIS), an antineoplastic agent, shows serious side effects such as hepatotoxicity. Thymoquinone (ThQ) is a powerful anti-oxidant with many beneficial effects such as anti-inflammatory, anti-tumoral. The aim of this study was to investigate whether ThQ treatment has hepatoprotective effect in CIS-induced hepatotoxicity model in rats and also to determine how CIS and/or ThQ treatments affect OTULIN levels, one of the deubiquitinases, in liver tissue. Materials and Methods: The 28 rats used in the study control (application not done), CIS (7 mg/kg CIS, first day of experiment, intraperitoneal), CIS+ThQ (7 mg/kg CIS, first day of experiment, intraperitoneal + 10 mg/kg/day ThQ, oral gavage) and ThQ (10 mg/kg/day ThQ, oral gavage) were divided into four equal groups (n=7). The experiment was terminated upon completion of all applications (day 15). The effects of CIS and\or ThQ apps on liver tissues were examined biochemically, histopathologically and immunohistochemically. Results: CIS application increased liver enzyme levels, histopathological changes, inflammation, oxidative stress and apoptosis in liver tissue and caused a decrease in OTULIN level. However, ThQ administration showed a positive regulatory effect on CIS-induced changes in liver tissue.. Conclusion: ThQ supplementation has a hepatoprotective effect against CISinduced liver tissue damage.